A royal wreck? Morpho-technological, elemental and lead isotope analysis of ingots from the Bang Kachai II shipwreck, Thailand. (April 2022) - Venunan, Pi; Ploymukda, Sira; Boripon, Borisut; Kwansakul, Pajaree; Suteerattanapirom, Kannika; Pryce, T.O.
Highlights: Two hundred metal ingots from the 17 th century shipwreck in Thailand were studied. Macro/microstructural, chemical, and lead isotopic analyses were performed. We provide insights into metal circulation beyond historical documents. Potential evidence for regional production of copper and lead discovered. Abstract: The Bang Kachai II wreck lies at 7–8 m depth in the Gulf of Thailand, just off the coast in the eastern Thai province of Chanthaburi. The ship, of which only the partial hull remains, probably sank in the early 17 th century CE. It carried a cargo of ca. 20, 000 billets, 10, 000 kg, of sappanwood and, the focus of this paper, up to 3, 000 kg of metal ingots. Sappanwood was an Ayutthaya state-controlled commodity, much prized abroad, China in particular, suggesting the vessel was possibly operating with Royal permission. Here we investigate the nature of the metal assemblage, to see if it supports or undermines this interpretation. Typo-technological analysis classified 195 copper ingots into four groups: layered bowl, bowl, plate, and irregular shape, but of non-standardised proportions. The five lead–tin alloy (pewter) ingots, on the other hand, share a single plano-convex shape. The ingots' elemental compositions were likewise variable, with a majority in raw/black (sulphur content) copper but a substantial minority in leaded copper, of a range of alloy proportions, as well as bronze, leaded bronze, pewter and the intermetallic semi-product, matte. A representative group of 20 artefacts were sub-sampled for lead isotope analysis, the results of which separated into two main groups. The larger group, representing both leaded and unleaded alloys, does not correspond to any of the known Southeast Asian production signatures but does fall into the general field of regional consumption signatures. The smaller group corresponds to the five pewter ingots, and their LI signature is consistent with the Song Toh lead field, located ca. 200 km west of Ayutthaya. The copper's physical and geochemical variability is not consistent with any known regional producers and thus their provenancing could not be resolved in this paper. However, this paper, based on sappanwood and lead-base ingots, opens new possibilities of copper being locally produced in Thailand, if not intra-regionally in Southeast Asia.